2021
DOI: 10.1002/ieam.4507
|View full text |Cite
|
Sign up to set email alerts
|

Application of multimedia models for understanding the environmental behavior of volatile methylsiloxanes: Fate, transport, and bioaccumulation

Abstract: Multimedia fate and transport models (MFTMs) describe how chemicals behave in the environment based on their inherent properties and the characteristics of receiving systems. We critically review the use of MFTMs for understanding the behavior of volatile methylsiloxanes (VMS). MFTMs have been used to predict the fate of VMS in wastewater treatment, rivers, lakes, marine systems, and the atmosphere, and to assess bioaccumulation and trophic transfers. More widely, they have been used to assess the overall pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 137 publications
(283 reference statements)
0
4
0
Order By: Relevance
“…Due to the properties of persistent, bioaccumulative, toxic and long-range atmospheric transport, cVMS are currently being considered as emerging persistent organic pollutants (POPs) for regulation. 14 Recent results have also detected low-volatility siloxanes in the particle phase from indoor cooking events 15 or ship emissions. 16 Evidence from laboratory studies indicated that oxidized cVMS products could also contribute to the formation of secondary organosiloxane aerosol (SOSiA), 17,18 especially decamethylcyclopentasiloxane (D 5 -siloxane, C 10 H 30 O 5 Si 5 ), the most abundant siloxane in urban areas.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to the properties of persistent, bioaccumulative, toxic and long-range atmospheric transport, cVMS are currently being considered as emerging persistent organic pollutants (POPs) for regulation. 14 Recent results have also detected low-volatility siloxanes in the particle phase from indoor cooking events 15 or ship emissions. 16 Evidence from laboratory studies indicated that oxidized cVMS products could also contribute to the formation of secondary organosiloxane aerosol (SOSiA), 17,18 especially decamethylcyclopentasiloxane (D 5 -siloxane, C 10 H 30 O 5 Si 5 ), the most abundant siloxane in urban areas.…”
Section: Introductionmentioning
confidence: 98%
“…Due to the properties of persistent, bioaccumulative, toxic and long-range atmospheric transport, cVMS are currently being considered as emerging persistent organic pollutants (POPs) for regulation. 14…”
Section: Introductionmentioning
confidence: 99%
“…As such, recent studies have focused on the atmospheric chemistry of cVMS. D 5 is usually emitted in higher concentrations than other cVMS, with typical indoor and outdoor D 5 mixing ratios ranging from approximately 4 to 20 ppbv and from 0.4 to 20 pptv, respectively. , …”
Section: Introductionmentioning
confidence: 99%
“…14,16,22 OFRs use residence times that are on the order of minutes and oxidant concentrations that are typically 100−1000 times higher than ambient levels. Their ability to access photochemical aging time scales of up to several days was critical in previous studies examining D 5 + OH SOA formation as a result of the relatively long OH lifetime of D 5 . While these factors may make the chemistry and microphysics in the OFR somewhat different from the chemistry and microphysics in the atmosphere, 23,24 here, investigating D 5 Cl-SOA formation in an OFR enables a more direct comparison of the relative SOA yields obtained via OH and Cl oxidation (hereafter referred to as "OH-SOA" and "Cl-SOA", respectively).…”
Section: Introductionmentioning
confidence: 99%